"Anal Haq" and Injustice: A Sufi and Resistance Discourse in Sachal Sarmast’s “He Came to Know Himself” - Dr. Asma Ghulam Rasool; Tanzeela Arshaad; Dr. Hina Khan; Dr. Tahira Sarwar; Dr Arooba Masroor Siddiqui; Dr Faiza Kiran; Dr Shazia Razzaq (Kurdish Studies, 2024)
This research explored the complex and diverse impact of Sachal Sarmast, a highly respected Sindhi Sufi poet, by studying how his Sufi beliefs, societal criticism, and poetry structure interact with each other. This research utilized a qualitative methodology and adopts a historical-critical perspective. The research examined primary data including Sachal Sarmast's poem “He Came to Know Himself”, as well as secondary data derived from academic publications on Sindhi literature, Sufism, and the socioeconomic history of 18th-century Sindh. Textual analysis approaches are used to scrutinize the substance, linguistic elements, and stylistic decisions included in Sachal's poetry. A critical analysis is conducted using theoretical frameworks such as Fairclough's Social Context and Van Dijk's Ideology Analysis, as well as historical references to personalities such as Mansur al-Hallaj. Textual analysis approaches are used to detect themes, metaphors, symbols, and stylistic decisions in Sachal's poetry. This research focuses on how these aspects come together to represent both his Sufi ideas and his societal criticism. The research uncovers a unique blend of Sufi principles and societal critique in Sachal's poetry. He uses words and lyrical forms to communicate his love for the holy while also criticizing societal injustices. His combative attitude recalls the volatile period he lived in and speaks to the need for change. Sachal Sarmast's poetry illustrates the Sufi belief in Wahdat ul-Wujud (unity of existence) while also defying societal standards, expressing a distinct combination of self-sacrifice for social justice within the larger Sufi discourse on martyrdom and love. This research provides a deeper understanding of Sachal Sarmast's creativity, function as a social critique within Sufism, and long-standing contribution to Sindhi literature. It emphasizes the ability of poetry to articulate complicated concepts and advocate for social change.